ALPHA-LACTALBUMIN GENOTYPES IDENTIFICATION IN ROMANIAN BLACK SPOTTED CATTLE BREED - R.A. VĂTĂŞESCU-BALCAN; S.E. GEORGESCU; MARIA ADINA MANEA; ANCA DINISCHIOTU; C.D. TESIO; MARIETA COSTACHE (Scientific Papers Animal Science and Biotechnologies, 2023)
Alpha-lactalbumin (α-La) is a major milk protein essential for the biosynthesis of lactose at the level of mammary glands. α-La directly influences the quality and the volume of the milk since it is directly involved in the lactose synthesis (Ashwell et al., 1997). The PCR-RFLP test was performed to distinguish the different alleles in a population of Romanian Black Spotted cattle, a dairy breed. Genetic polymorphism was detected by digestion with the endonuclease MnlI, followed by electrophoresis in high resolution agarose gel stained with ethidium bromide. Sixty DNA samples from Romanian Black Spotted breed were analyzed for A and B variants. The PCRRFLP test makes feasible the inclusion of α-La genotypes in breeding plans and cattle selection.